IL-33 Acts to Express Schaffer Collateral/CA1 LTP and Regulate Learning and Memory by Targeting MyD88 - Tomoyuki Nishizaki (Neural Plasticity)
Interleukin-33 (IL-33) is recognized to transmit a signal through a heterodimeric receptor complex ST2/interleukin-1 receptor accessory protein (IL-1RAcP) bearing activation of myeloid differentiation factor 88 (MyD88). High-frequency stimulation to the Schaffer collateral induced long-term potentiation (LTP) in the CA1 region of hippocampal slices from wild-type control mice. Schaffer collateral/CA1 LTP in IL-33-deficient mice was significantly suppressed, which was neutralized by application with IL-33. Similar suppression of the LTP was found with MyD88-deficient mice but not with ST2-deficient mice. In the water maze test, the acquisition latency in IL-33-deficient and MyD88-deficient mice was significantly prolonged as compared with that in wild-type control mice. Moreover, the retention latency in MyD88-deficient mice was markedly prolonged. In contrast, the acquisition and retention latencies in ST2-deficient mice were not affected. Taken together, these results show that IL-33 acts to express Schaffer collateral/CA1 LTP relevant to spatial learning and memory in a MyD88-dependent manner and that the LTP might be expressed through an IL-1R1/IL-1RAcP-MyD88 pathway in the absence of ST2.